Hubungan Perilaku Minum Obat Dengan Tingkat Pengendalian Tekanan Darah Di Dusun Tamanan Kelurahan Tamanmartani - Seklin Geovani, Vincensia; Subiyanto, Paulus; Arif Wibowo , Tandean (Jurnal Kesehatan Saelmakers PERDANA (JKSP), 2026)
Hypertension is a chronic disease characterized by persistently elevated blood pressure and is known as a silent killer because it often shows no symptoms, but can cause serious complications if not properly controlled. Tamanan Hamlet is one of the areas in Sleman Regency with a fairly high number of hypertension sufferers. Based on a preliminary study, a total of 4,217 cases of hypertension were recorded at the Kalasan Community Health Center during 2024. The purpose of this study was to determine the relationship between medication-taking behavior and the level of blood pressure control in hypertension sufferers in Tamanan Hamlet. This study used a descriptive correlational method with a sample of 48 respondents with hypertension selected using a total sampling technique. Data were collected using a medication-taking behavior questionnaire and blood pressure measurements and data were taken on July 7-9, 2025. The results showed that the majority of respondents had poor medication-taking behavior as many as 41 people (85.4%) and uncontrolled blood pressure as many as 43 people (89.6%). The results of statistical tests using the Spearman test showed a p value of 0.833 for systolic blood pressure and p = 0.177 for diastolic blood pressure (p > 0.05), so it can be concluded that there is no significant relationship between medication-taking behavior and the level of blood pressure control. Therefore, hypertension control does not only depend on medication-taking behavior, but also needs to be supported by healthy lifestyle changes, ongoing education, and adequate social and family support.